2017
DOI: 10.1007/s00590-017-2071-0
|View full text |Cite
|
Sign up to set email alerts
|

Cementless modular neck stems: are they a safe option in primary total hip arthroplasty?

Abstract: The findings in the present study showed that the H-MAX-M stem provided satisfactory functional outcome in most patients with a low rate of complications attributable to the modular neck design. We consider that using this novel modular neck-stem coupling design can be an alternative to the conventional monoblock stems in patients without overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Five studies 24 , 26 , 31 , 41 , 42 reported cobalt and chromium ion serum levels in ng/ml, that are summarized in Table 4 . Only one paper 41 evaluated systemic metal ion levels in a homogenous series of patients after implantation of a mixed-alloy modular neck hip prosthesis (Symbios SPS, Ti stems coupled to Co-Cr necks) compared to those of two control groups: a group of patients having received the non-modular neck version of the same stem (Ti6Al4V) and a group of patients without any metal implant.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 24 , 26 , 31 , 41 , 42 reported cobalt and chromium ion serum levels in ng/ml, that are summarized in Table 4 . Only one paper 41 evaluated systemic metal ion levels in a homogenous series of patients after implantation of a mixed-alloy modular neck hip prosthesis (Symbios SPS, Ti stems coupled to Co-Cr necks) compared to those of two control groups: a group of patients having received the non-modular neck version of the same stem (Ti6Al4V) and a group of patients without any metal implant.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, some studies have reported satisfactory results using dual modular stems in primary THAs [ 106 , 107 , 108 ]. Specific dual modular stems offer a better reconstruction of hips that deviate from standard anatomy when compared to a monoblock arthroplasty system with different offset options [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 25 case reports 1640 and 7 clinical studies. 5,7,4145 Figure 1 demonstrates the study selection process based on PRISMA guidelines. 2 authors independently assessed the potential risk of bias of the included clinical studies based on MINORS criteria.…”
Section: Resultsmentioning
confidence: 99%
“…3 out of 7 were considered as low risk of bias, 7,43,45 while 4 out of 7 as high risk of bias. 5,41,42,44 The latter was considered as high due to retrospective design, inadequate blinding of endpoints and low rate of patients.…”
Section: Resultsmentioning
confidence: 99%